Pendampingan Pembentukan Kader Hulu Sampah Di Desa Minggirsari Kabupaten Blitar - Masrunik, Endah; Andriawan, Aris Heri; Jatmiko, Dheny; Khomariah, Nuril Esti (Cattleya Darmaya Fortuna, 2025)
The aim of implementing this community service is to form upstream waste cadres in Minggirsari Village, so that existing waste can be managed well and the community has motivation in managing their household waste. The implementation method for this activity is carried out by holding socialization about the upstream waste cadres of Minggirsari Village, which is then provided with ongoing assistance so that the upstream waste can work according to its function and is able to increase the number of waste bank members. The result of this activity is the formation of upstream waste cadres in Minggirsari, household waste is well managed, this is proven by the increasing number of waste bank members and the increasingly active existing waste banks. Apart from that, with the assistance provided by the upstream waste cadres, they are increasingly active in holding socialization or education on the importance of sorting waste and realizing several blessing sacks of waste in